Комп'ютерна програма «sort savvy» при вивченні питань захисту літосфери від забруднення відходами - Внуков, Т. С. (ХНУРЕ, 2024)
A new computer program "Sort Savvy" has been created, which illustrates how owners of industrial and residential complexes can effectively sort waste and evaluate the benefits of this process. The main emphasis is on the visual demonstration of the consequences of anthropogenic human activity, its impact on people and the environment. Methods of solving these issues are also proposed. The program is designed for assimilation and consolidation of knowledge on environmental safety and life safety.
Keywords: захист літосфери; забруднення відходами